ИЗУЧЕНИЕ ДЕЙСТВИЯ ЭКЗОГЕННОЙ Н2О2 НА ЖИЗНЕСПОСОБНОСТЬ КЛЕТОК АЛЕЙРОНОВОГО СЛОЯ ЗЕРНА ПШЕНИЦЫ (Experimental biology, 2017)
In present work we show that an intact aleurone tissue in presence of gibberellic acid possesses a significant capacity of utilizing exogenous Н2О2 during first 24 hours of incubation. Subsequent increase of incubation time leads to dramatic attenuation of Н2О2 utilization. Conversely, abscisic acid-treated aleurones retain the Н2О2-utilizing capability throughout the whole incubation period. The effect of GA is coincident with maximal decrease in SOD activity. Supposedly, ABA retards a О2• generation in aleurone cells via activation of SOD. The strong correlation between the time of aleurone layer PCD onset, О2• generation and oscillation of SOD activity is observed.
Keywords: incubation; aleurone